Wetlandscape : towards an expanded definition of edges : [an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design, Massey University, Wellington, New Zealand] - Clarkin, Jessica (Massey University, 2014)
Over the course of an afternoon walk I explore and critically reflect on my Master of Design project Wetlandscape. I look to expand the definition of edges through the design of a walkway within their complex of beautiful native wetlands on the Rarangi vineyard for industry partner Wither Hills. This project is deeply rooted in ecology and uses design as a tool to deal directly with the implications of the eradication of wetlands within New Zealand. Wither Hills and I look toward a future of restoration and maintenance of these natural zones. The poetic journey through the site traverses through eight evocative follies designed to encourage wine tourism enhanced by site-specific design. I discover the ubiquitous quality of architecture to generate mood and atmosphere through sensitive treatment of materials and space. As a spatial designer I engage in the realms of landscape architecture, architecture and design to traverse the field of space making in the landscape. This text describes the wanderlust of design through the production of a landscape narrative which positions the sensate body as an important figure in enabling unique experiences within architecture and environment.
Keywords: Wetlands landscape design; Wither Hills; Landscape architecture